Defect Healing in FAPb(I1‐xBrx)3 Perovskites: Multifunctional Fluorinated Sulfonate Surfactant Anchoring Enables >21% Modules with Improved Operation Stability. Issue 20 (7th April 2022) - Zhu, Jun; Qian, Yongteng; Li, Zijia; Gong, Oh Yeong; An, Zongfu; Liu, Qing; Choi, Jin Hyuk; Guo, He; Yoo, Pil Jin; Kim, Dong Hoe; Ahn, Tae Kyu; Han, Gill Sang; et al.
Abstract: Formamidinium lead triiodide‐based perovskite solar cells have emerged as one of the most promising candidates that can be potentially used to develop photovoltaic technologies in the future. The commercial use of perovskite solar cell modules (PSCMs) is limited as it is challenging to fabricate high‐quality, efficient, and stable large‐area perovskite light‐absorbing films. Heptadecafluorooctanesulfonic acid tetraethylammonium salt (HFSTT), containing fluorinated long alkyl chains as hydrophobic tails and sulfonic acid groups (SO3 − ) as hydrophilic heads, which exhibit a great synergistic potential in large‐area film uniform fabrication, crystallization orientation modulation, defect passivation, and device operation stability enhancement, are introduced. The HFSTT‐modified films exhibit a prominent (100) orientation and lower trap‐state density as well as enhanced carrier mobilities and diffusion lengths, facilitating a champion unit device with an impressive power conversion efficiency (PCE) of 23.88% (0.14 cm 2 ) and 22.52% (1 cm 2 ) with a low voltage deficit around 0.341 V. The unencapsulated device retains ≈70% of its initial efficiency after 1000 h under heat damping test (60 °C and ≈60% RH). Moreover, the PSCMs exhibiting PCEs of 21.05% (with notable fill factor 0.79) and 18.27% are characterized by the active areas of 25.98 and 60.68 cm 2, respectively. Abstract : A multifunctional sulfonate surfactant anchoring strategy is introduced for regulating perovskite precursor solution surface tension, retarding the perovskite crystallization and hindering the tilting of the grains, leading to full‐coverage uniform large‐area perovskite layers with high crystallinity as well as low trap densities. The target modules achieve power conversion efficiencies of 21.05% (stabilized power output around 20.4%) on active areas of 25.98 cm 2 .